2020
DOI: 10.1155/2020/8690540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Functional Movement Screen, Star Excursion Balance Test, and Physical Fitness in Junior Athletes with Different Sports Injury Risk

Abstract: Objectives. The aim of this study was to assess the relationships between functional movement screen (FMS), star excursion balance test (SEBT), agility T test, and vertical jump test scores and sports injury risk in junior athletes. We compared these assessments and the differences between groups with high and low risks of sports injury. Subjects and Methods. Eleven volleyball, 12 basketball, and 9 handball athletes were recruited. All participants followed the routine training in school sports teams. Weekly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 27 publications
3
27
0
2
Order By: Relevance
“…Chimera et al [20] showed that worse ranges of motion in the hip and knee joints negatively affect the movement patterns quality in a mixed study sample. The same authors [18] also observed that stronger trunk muscles positively influenced the FMS scores. Surprisingly, in our research, a higher score in trunk stability push-up (TSPU) was not directly associated with a better result of the sit-ups, whereas the study by Silva et al [20,21] found links between the trunk stability push-up (TSPU) and the physical fitness of the study group.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Chimera et al [20] showed that worse ranges of motion in the hip and knee joints negatively affect the movement patterns quality in a mixed study sample. The same authors [18] also observed that stronger trunk muscles positively influenced the FMS scores. Surprisingly, in our research, a higher score in trunk stability push-up (TSPU) was not directly associated with a better result of the sit-ups, whereas the study by Silva et al [20,21] found links between the trunk stability push-up (TSPU) and the physical fitness of the study group.…”
Section: Discussionmentioning
confidence: 77%
“…Support for these results can be found in the studies by Campa et al [17]. Chang et al [18] indicated the relationship between a trunk stability push-up with agility t-test result. Sannicandro et al [19] showed a connection between the FMS score and the power of the lower limbs among professional footballers, showing that better quality of movement patterns was associated with greater power of the lower limbs.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The assumption is that higher levels of movement competency (as represented by higher FMS scores) provides some protection from injury. Contrary to the findings of a threshold FMS score that is predictive of injury rates in adults, the composite FMS score has consistently been found to be a poor predictor of injury rates in young athletes in a variety of sports [43,51,72,79,80,94,[99][100][101][102]107].…”
Section: The Fms In Youth Sports and Risk Of Injuriesmentioning
confidence: 99%
“…Functional movement screening [13][14][15] is a test model proposed by American orthopedic training experts in 1996.…”
Section: Introductionmentioning
confidence: 99%